2022
DOI: 10.1186/s12870-022-03764-w
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of plant growth regulators production from microalgae cultivated in treated sewage wastewater (TSW)

Abstract: The aim of this work is to develop an efficient method for detection and evaluation of the plant growth regulators produced from cyanobacteria species (Anabaena oryzae and Nostoc muscorum) cultivated on BG110, and Chlorophyta alga (Chlorella vulgaris) cultivated on BG11 in addition to the cultivation of these strains on treated sewage wastewater (TSW) combined with control media (BG11 and BG110) at different concentrations (100, 75 and 50%). Bioassays were performed on Wheat coleoptile length and Cucumber coty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…En estas etapas apoyaron la formación de foto-asimilados formados en las hojas al mejorar el crecimiento del fruto. Los azúcares administrados de forma exógena (por la miel), actuaron de forma energética sobre la división y elongación celular [24], los aminoácidos, vitaminas, fenoles y flavonoides, aplicados de forma exógena, favorecieron a la biosíntesis de compuestos estructurales y de hormonas para aumentar el crecimiento celular del fruto, al acelerar el metabolismo, dando como resultados cambios fisiológicos importantes y el aprovechamiento eficientes de todos los componentes indispensables para que este órgano creciera [25].…”
Section: Discussionunclassified
“…En estas etapas apoyaron la formación de foto-asimilados formados en las hojas al mejorar el crecimiento del fruto. Los azúcares administrados de forma exógena (por la miel), actuaron de forma energética sobre la división y elongación celular [24], los aminoácidos, vitaminas, fenoles y flavonoides, aplicados de forma exógena, favorecieron a la biosíntesis de compuestos estructurales y de hormonas para aumentar el crecimiento celular del fruto, al acelerar el metabolismo, dando como resultados cambios fisiológicos importantes y el aprovechamiento eficientes de todos los componentes indispensables para que este órgano creciera [25].…”
Section: Discussionunclassified
“…The IAA-producing microalgae C. vulgaris resulted in high leaf numbers, long shoots, and significant root initiation without branching and leaf expansion. Similarly, Anabaena oryzae and N. muscorum stimulated a 1.5-fold increase in the fresh weight of soybean callus [ 102 ]. Furthermore, the auxin derived from the mangrove-root-associated cyanobacterium Phormidium sp.…”
Section: Microalgae As Biostimulantsmentioning
confidence: 99%
“…A recent study revealed that Stigeoclonium nanum , a cytokinin-derived microalga, contains cis-zeatin and isopentenyladenine (21.40 nmol g −1 DW), which were found to be the most predominant compounds, followed by trans-zeatin and dihydrozeatin in low levels, in addition to free bases and their ribosides [ 99 ]. Moreover, benzyl adenine, found in the algal extract of A. oryzae and N. muscorum , significantly enhanced shoot length and leaf number, leading also to high root initiation, in tomatoes [ 102 ]. Cytokinins derived from Desmodesmus subspicatus extracts grant a 30% increase in plant biomass, enhanced cell division, leaf chlorophyll contents, enhanced fresh weight, and increased cotyledon size in cucumbers [ 107 ].…”
Section: Microalgae As Biostimulantsmentioning
confidence: 99%
“…that allowed these components to pass through the cuticle of the fruits, were inducers of cell elongation and division in stage two. According to Caballero-Pérez [47], in the growth stage that involves division and expansion, there is competition for carbohydrate sources, according to Pérez-Barraza [48], during the cell expansion of the fruit metabolic components are needed to synthesize hormones and compounds that allow the generation of tissue, and Elakbawy [50], indicates that organic compounds from plant sources, exogenous or endogenous to the tissue influence physiological processes that control cell division and the differentiation of the growth process, in which cell elongation is involved, finding the participation of sulfur amino acids, auxins and cytokinins.…”
Section: Dynamics Of Fruit Growth In the Mango (A) And Rambután (B) C...mentioning
confidence: 99%